Recruitment and Selection Process in Restaurant and Café Industry in Malang City - Juariyah, Lohana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
This study aimed to explore the recruitment and selection process in food and beverages industry to gain high-qualified workers. By using phenomenology approach through in-depth interview and field observation, the study figured out that there was a specific characteristic process of recruitment and selection in this business. The recruitment process was carried out within the conditions: (1) there was no periodical/scheduled recruitment, (2) it was conducted since new employees were required, (3) it was mostly based on external sources, and (4) the utilization of social media, i.e., BBM, Instagram, and Twitter as recruitment channels. While there was two main activities in the selection process: (1) Generally, applicants were selected based on four tests: administrative test, knowledge and skill test, managerial interview, and the owner interview as the final test; (2) Four standard indicators were used to evaluate the candidate: a) Administrative indicator: candidate should have experience dealing with the applied job and the certificate final score is +75 in average; b) Physical indicator: candidate should have good-looking, clean and charming appearance; c) Skills indicator: candidate should know and understand the job task precisely; d) Communication indicator: candidate should have communicative skills, fluent and confident during the interview.